Transoesophageal echo-guided mitral valve repair using the Harpoon system. (30th October 2017) - Gerosa, Gino; D'Onofrio, Augusto; Besola, Laura; Colli, Andrea
Abstract: Transapical off-pump echo-guided mitral valve repair with implantation of artificial ePTFE chordae with the Harpoon device has been proposed to treat patients presenting with severe mitral regurgitation due to posterior leaflet prolapse. The device is inserted in the left ventricle and steered to the surface of the diseased portion of the leaflet. The Harpoon device is actuated, and the leaflet is perforated by a needle that consequently releases an ePTFE chord that is fixed on the atrial surface by a double-helix coiled knot. The chord is then tensioned and fixed on the epicardial surface of the ventricle under echocardiography guidance.